The Importance of E-Construction Implementation in the Syrian Projects - عمران, جمال (Latakia University Journal -Engineering Sciences Series, 2020)
Did we have in Syria the need to implement the E-Construction in our projects? This question seems to be very significant; when we know that, a lot of the industry obstacles and problem can be easiest using E- Construction tools. Construction industries are internationally today in rabid development of E-Business and other technologies to increase productivity and performance. In this paper, I demonstrate the effective utilizing of the E-Construction tools in a pumping station project to elucidate the benefits, opportunities and challenges of Information and communication Technology (ICT) and E-Business in Syrian construction industry. New technology using ICT and E-Business brings changes in construction industries. ICT applications improve workflow and communication in diverse levels of organization. ICT and E-Business are important to both large and small enterprises facilitating integration and collaboration with business partners, suppliers and customers and to make electronic transactions. Syrian construction companies are not yet started adopting speedy communication tools to get efficient work done.